Changes in Human Milk Immunoglobulin Profile During Prolonged Lactation - Czosnykowska-Łukacka, Matylda; Lis-Kuberka, Jolanta; Królak-Olejnik, Barbara; Orczyk-Pawiłowicz, Magdalena (Frontiers in Pediatrics, 2020)
Mother’s milk immunoglobulins (Igs) delivered to infants during breastfeeding are crucial in shaping and modulating immature infants’ immune system and provide efficient protection against pathogens. The aim of the study was to evaluate immunoglobulin concentrations in milk of 116 lactating mothers over prolonged lactation from the 1st to the 48th month using the ELISA method. The concentration of proteins SIgA and IgG, but not IgM, showed a positive correlation (r=0.69, p<0.005; r=0.54, p<0.05; and r=0.27, p<0.05) with lactation from the 1st to 48th month. The lowest concentrations of SIgA and IgG were observed for the first year (2.12±0.62 g/L and 14.71±6.18 mg/L) and the highest for after the 2nd year of lactation (7.55±7.16 g/L and 18.95±6.76 mg/L). The IgM concentration remained stable during 2 years (2.81±2.74 mg/L), but after 24 months it was higher (3.82±3.05 mg/L), although not significantly. Moreover, negative correlations of protein (r=-0.24, p<0.05) and SIgA (r=-0.47, p<0.05) concentrations with the number of feedings were found. Human milk after the 2nd year of lactation contains significantly higher concentrations of protein, SIgA, and IgG. High concentration of immunoglobulins and protein during prolonged lactation is an additional argument to support breastfeeding even after introducing solid foods and should be one of the overarching goals in the protection of children’s health.